2020
DOI: 10.1111/adb.12932
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Tlr3 reduces acute tolerance to alcohol and alcohol consumption in the intermittent access procedure in male mice

Abstract: Pharmacological studies implicate toll‐like receptor 3 (TLR3) signaling in alcohol drinking. We examined the role of TLR3 in behavioral responses to alcohol and GABAergic drugs by studying Tlr3 −/− mice. Because of opposing signaling between TLR3 and MyD88 pathways, we also evaluated Myd88 −/− mice. Ethanol consumption and preference decreased in male but not in female Tlr3 −/− mice during two‐bottle choice every‐other‐day (2BC‐EOD) drinking. There were no genotype differences in either sex during continuous o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Following ethanol intake, TLR2, TLR3, TLR4, and TLR7 expression increases in the mouse prefrontal cortex, another important area involved in cognitive function [69]. Ethanol-induced TLR3 activation increases the expression of inflammatory IL-1β, IL-6, and TNF in the hippocampus [70], as well as voluntary alcohol intake [71,72]. TLR2 and TLR4 knockout rodents are protected from ethanol-induced neuroinflammation [73],…”
Section: Traumatic Injuriesmentioning
confidence: 99%
“…Following ethanol intake, TLR2, TLR3, TLR4, and TLR7 expression increases in the mouse prefrontal cortex, another important area involved in cognitive function [69]. Ethanol-induced TLR3 activation increases the expression of inflammatory IL-1β, IL-6, and TNF in the hippocampus [70], as well as voluntary alcohol intake [71,72]. TLR2 and TLR4 knockout rodents are protected from ethanol-induced neuroinflammation [73],…”
Section: Traumatic Injuriesmentioning
confidence: 99%
“…Congruent with these findings, studies in animals demonstrated that TLR4 may have an essential and underappreciated role in reward-related behaviors induced by alcohol ( June et al, 2015 ), morphine ( Hutchinson et al, 2012 ), and cocaine ( Kashima and Grueter, 2017 ). In addition, the TLR3 and TLR2 signaling pathways were shown to increase cocaine consumption ( Blednov et al, 2017 ; Zhu et al, 2018 ; Blednov et al, 2020 ). Furthermore, cocaine alone is sufficient to upregulate the expression of other cytokines including NF-κβ ( Zhu et al, 2021 ), TNF-α ( Lewitus et al, 2016 ; Brown et al, 2018 ), IL-1β ( Northcutt et al, 2015 ), and IL-8 ( Meckel and Kiraly, 2019 ), which in turn enhances dopamine release and finally exaggerates the drugs-mediated behavioral response.…”
Section: Potential Mechanisms Underlying the Effects Of Glp-1ras On C...mentioning
confidence: 99%
“…Expression of TLR3 receptors is increased following alcohol intake (Warden et al, 2019a)and treatment with the TLR3 agonist polyinosinic:polycytadylic acid (poly(I:C)) increases alcohol intake in mice and rats (Qin and Crews, 2012;Randall et al, 2019;Warden et al, 2019a, b). Furthermore, genetic knockout of TLR3 not only decreases alcohol intake but also decreases acute tolerance to alcohol in male mice further suggesting an important role of TLR3 in both alcohol intake and physiological response to alcohol (Blednov et al, 2021).…”
Section: Introductionmentioning
confidence: 97%